From Chalk to Click: Elevating Information Technology Literacy Among Digital Immigrant Teachers in Bandar Lampung - Windah, Andi; Nurhaida, Ida; Aryanti, Nina Yudha (CV. Literasi Indonesia, 2024)
The Elevating IT Literacy Among Digital Immigrant Teachers in Bandar Lampung aims to improve the digital skills of teachers in Indonesia by empowering teachers to integrate technology into their teaching. The initiative provides tailored training for elementary school teachers to enhance their digital proficiency and use digital tools effectively in their teaching. The transition implementation enhances ICT integration in classroom teaching, improving interactivity, accessibility, student engagement, and learning outcomes. The initiative took place at SDN 3 Sukajawa Bandar Lampung and resulted in a significant improvement in teachers' digital literacy, with a 33% increase. 25% increase in knowledge post-training program. The educational interventions narrowed the digital proficiency gap between educators and tech-savvy students. The program's success is evident in the teachers' enhanced ability to develop and use digital instructional materials, which are essential for creating an engaging learning environment. In the rapidly changing educational landscape, it's crucial to implement programs like this to ensure that teachers can effectively address their students' diverse needs in the digital era.